2021
DOI: 10.1021/acsami.1c14831
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Fabrication of Nanoceria with Oxidase-like Activity at Neutral pH: Mechanism and Boosted Bio-Nanozyme Cascades

Abstract: Catalytic cascades have drawn much attention by avoiding the isolation of intermediates and due to high atom economy. Yet, developing an efficient, one-pot biocatalytic cascade remains challenging. Combined with the selectivity of biological enzymes and tunable activity of nanozymes, we herein demonstrate an effective bio-nanozyme cascade formed by glucose oxidase (GOx) and in situ-generated nanoceria. The prepared H2O2–nanoceria complex shows strong oxidative activity for common chromogenic substrates under p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…In the current situation, it is still a challenge that the OXD activity is low at physiological pH. , As a result, Zhang et al found that glucose oxidase CeO 2 NMs induced a cascade-nanozyme in which chromogenic substrates exhibited strong oxidative reactions. This study provides a new idea for promoting biomimicry catalytic cascade reactions in neutral conditions.…”
Section: Catalytic Mechanism Of Ceo2 Nmsmentioning
confidence: 99%
“…In the current situation, it is still a challenge that the OXD activity is low at physiological pH. , As a result, Zhang et al found that glucose oxidase CeO 2 NMs induced a cascade-nanozyme in which chromogenic substrates exhibited strong oxidative reactions. This study provides a new idea for promoting biomimicry catalytic cascade reactions in neutral conditions.…”
Section: Catalytic Mechanism Of Ceo2 Nmsmentioning
confidence: 99%
“…Numerous strategies have been developed to enhance the selectivity of nanozyme-based sensors, including the design of bio-nanozyme cascades, [11][12][13][14] nanozyme-linked immunoassays, 15,16 and DNA/aptamer-coupling systems. 5,7 Among them, cascade catalysis has attracted much attention due to the superiority of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of two ionic valencies (Ce 3+ /Ce 4+ ) on the active sites of nanoceria is responsible for the oxygen vacancy generation on the surface, which facilitates the phosphohydrolase activity of CeO 2 NPs. Because of their ionic valency state, they behave as radical scavengers . Nanoceria exhibit pH-dependent variation of surface charges (negative, positive, or neutral) and other specific properties like homogenization, dispersion, and stabilization in aqueous solutions, which help in its application as oxidase, catalase, biomolecule adsorbent, sensors, , etc. Recent advancements in research have proven the enzyme mimetic like activity and catalytic phosphorylation activity of CeO 2 NPs with several biomolecules such as DNA, RNA, nucleic acid, and peptides. …”
Section: Introductionmentioning
confidence: 99%
“…Nanoceria exhibit pH-dependent variation of surface charges (negative, positive, or neutral) and other specific properties like homogenization, dispersion, and stabilization in aqueous solutions, which help in its application as oxidase, catalase, biomolecule adsorbent, sensors, , etc. Recent advancements in research have proven the enzyme mimetic like activity and catalytic phosphorylation activity of CeO 2 NPs with several biomolecules such as DNA, RNA, nucleic acid, and peptides. …”
Section: Introductionmentioning
confidence: 99%